Perovskite thin film and method for interface modification of perovskite thin film

By modifying the symmetric conjugated structural compounds containing fluorine on perovskite films, the problem of perovskite layer stability is solved, the humidity, thermal and light stability of perovskite solar cells is improved, and its use is extended life.

CN119233656APending Publication Date: 2024-12-31TRINA SOLAR CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411236182.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-04
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The stability of the perovskite solar cell layer is easily affected by oxygen, light, moisture and temperature, especially under ultraviolet radiation and local high temperatures, which leads to accelerated degradation of the perovskite layer, and defects in the film affect their performance and stability. sex.

Method used

Using fluorine-containing symmetric conjugated structural compounds as passivating agents to modify the upper and lower interfaces and surrounding interfaces of the perovskite film, form a protective barrier, prevent moisture penetration, improve thermal stability and light stability, reduce pyrolysis temperature, absorption and Scattering part of the incident light energy.

Benefits of technology

It significantly improves the long-term stability and performance of perovskite solar cells, extends the service life of perovskite films, and enhances its tolerance to humidity, oxygen and light.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119233656A_ABST
    Figure CN119233656A_ABST
Patent Text Reader

Abstract

The invention provides a perovskite thin film and a method for interface modification of the perovskite thin film, and particularly provides the perovskite thin film, the perovskite thin film is modified with a passivating agent, and the passivating agent comprises a fluorine-containing symmetrical conjugated structure compound. By modifying the upper interface, the lower interface and the periphery of the perovskite thin film with the passivator, multiple protection effects can be achieved, namely, passivator modification layers can form a protective barrier to prevent external moisture and moisture from entering the perovskite thin film, moisture permeation is effectively reduced, and the perovskite thin film is protected against moisture erosion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of solar cells, and in particular, to a perovskite film and a method for interface modification of the perovskite film. Background Art

[0002] Highly efficient organic-inorganic hybrid perovskite solar cells have become one of the most promising light-absorbing materials due to their excellent optoelectronic properties such as long carrier diffusion length and high absorption coefficient.

[0003] However, the stability of the perovskite layer is easily affected by factors such as oxygen, light, moisture and temperature. Especially under the action of ultraviolet radiation, in addition to the light itself, local high temperature can also cause ion migration inside the perovskite layer, thereby accelerating the degradation process of the perovskite. In addition, the defects in the perovskite film as the center of non-radiative recombination will also have a negative impact on its performance and stability.

[0004] Therefore, it is necessary to develop a method that can simultaneously improve the humidity stability, light stability and thermal stability of the perovskite layer. Summary of the invention

[0005] The present application aims to solve at least one of the technical problems existing in the prior art to at least a certain extent.

[0006] Therefore, in the first aspect of the present application, the present application proposes a perovskite film. According to an embodiment of the present application, the perovskite film is modified with a passivator, and the passivator includes a fluorine-containing symmetrical conjugated structure compound. Fluorine is an element with strong electronegativity, and the symmetrical conjugated structure generally has strong adsorption capacity and surface activity. Therefore, the use of a fluorine-containing symmetrical conjugated structure compound as a protective agent can ensure that it is effectively bonded and adsorbed on the surface of the perovskite film, thereby protecting the perovskite film.

[0007] According to an embodiment of the present application, the passivator is modified on the upper and lower interfaces and the surrounding interfaces of the perovskite film. By modifying the upper and lower interfaces and the surroundings of the perovskite film with a fluorine-containing symmetrical conjugated structure compound, multiple protection effects can be achieved, that is, these passivator modified layers can form a protective barrier to prevent external water and moisture from entering the interior of the perovskite film, effectively reduce the penetration of water, protect the perovskite film from water erosion, and achieve full enclosed protection of the perovskite film. In addition, these passivator modified layers can also improve the thermal stability and light stability of the perovskite film, which can not only reduce the pyrolysis temperature of the perovskite material and slow down the pyrolysis reaction, but also absorb and scatter part of the energy of the incident light, reduce the damage of the light energy to the perovskite film, and improve the long-term stability and performance of the perovskite solar cell.

[0008] In a second aspect of the present application, the present application proposes a method for interface modification of a perovskite film. According to an embodiment of the present application, the method comprises: immersing the perovskite film to be modified in an organic solvent containing a passivating agent to obtain a perovskite film with the interface modified with the passivating agent on all sides.

[0009] Through this method, the upper interface and surrounding interfaces of the perovskite film can be effectively modified, and these modifications can achieve multiple protection effects, that is, these passivator modified layers can form a protective barrier to prevent external water and moisture from entering the interior of the perovskite film, effectively reduce the penetration of water, and protect the perovskite film from water erosion. In addition, these passivator modified layers can also improve the thermal stability and light stability of the perovskite film, not only can they reduce the pyrolysis temperature of the perovskite material and slow down the pyrolysis reaction, but they can also absorb and scatter part of the energy of the incident light, reduce the damage of the light energy to the perovskite film, and improve the long-term stability and performance of the perovskite solar cell.

[0010] According to an embodiment of the present application, the method may further include at least one of the following additional technical features:

[0011] According to an embodiment of the present application, the perovskite thin film to be modified is formed by performing a first coating process of a perovskite thin film material on a substrate.

[0012] According to an embodiment of the present application, before the first coating treatment, a second coating treatment of an organic solvent containing a passivating agent is performed on the substrate; and the substrate coated with the organic solvent containing the passivating agent is subjected to a first annealing treatment.

[0013] According to an embodiment of the present application, the passivating agent includes a fluorine-containing symmetrical conjugated structure compound.

[0014] According to an embodiment of the present application, the fluorine-containing symmetrical conjugated structure compound is a compound containing hexafluoropropane.

[0015] According to an embodiment of the present application, the hexafluoropropane-containing compound includes at least one of 2,2-bis(4-aminophenyl)hexafluoropropane, 2,2-bis(4-carboxyphenyl)hexafluoropropane, 2,2-bis(3,4-xylyl)hexafluoropropane, 2,2-bis(3-nitrophenyl)hexafluoropropane, 2,2-bis(4-methylphenyl)hexafluoropropane, 2,2-bis(4-isocyanatophenyl)hexafluoropropane, 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane and 2,2-bis[4-(4-aminophenoxybenzene)]hexafluoropropane.

[0016] According to an embodiment of the present application, the organic solvent includes isopropanol, methanol or chlorobenzene.

[0017] According to an embodiment of the present application, the concentration of the fluorine-containing symmetrical conjugated structure compound in the organic solvent is 0.5 mol / L to 1 mol / L.

[0018] According to an embodiment of the present application, the soaking treatment time is 3s to 5s.

[0019] According to an embodiment of the present application, the method further includes: subjecting the perovskite film after the immersion treatment to a spin-drying treatment; and subjecting the perovskite film after the spin-drying treatment to a second annealing treatment.

[0020] According to an embodiment of the present application, the spin drying process is performed at 4800 rpm to 5200 rpm.

[0021] According to an embodiment of the present application, the spin drying process takes 20 seconds to 30 seconds.

[0022] According to an embodiment of the present application, the second annealing treatment is performed at 80-120°C.

[0023] According to an embodiment of the present application, the time of the second annealing treatment is 7 minutes to 10 minutes.

[0024] According to an embodiment of the present application, the first annealing treatment is performed at 100-110°C.

[0025] According to an embodiment of the present application, the time of the second annealing treatment is 5 minutes to 7 minutes.

[0026] In the third aspect of the present application, the present application proposes a perovskite film. According to an embodiment of the present application, the perovskite film is prepared by the method described in the second aspect. As mentioned above, the method of the present application can modify the upper and lower interfaces and the surrounding interfaces of the perovskite film to form a fully enclosed protective layer. Therefore, the perovskite film prepared by this method has strong stability, and the protective layer can prevent the perovskite film from contacting with adverse factors in the external environment (such as humidity, oxygen, light, etc.), reducing the damage and degradation to it, thereby extending the service life of the perovskite film; in addition, the perovskite film has good photoelectric properties and interface compatibility with other functional layers. The presence of the protective layer regulates the band structure, surface charge and interface electron transport characteristics of the perovskite film, thereby improving the photoelectric conversion efficiency, light absorption capacity and carrier transport efficiency.

[0027] In the fourth aspect of the present application, the present application proposes a perovskite solar cell. According to an embodiment of the present application, the perovskite solar cell includes: a substrate; a first charge transport layer, the first charge transport layer is arranged on one side of the substrate; a perovskite absorption layer, the perovskite absorption layer includes the perovskite film described in the third aspect, the perovskite absorption layer is arranged on the side of the first charge transport layer away from the substrate; a second charge transport layer, the second charge transport layer is arranged on the side of the perovskite absorption layer away from the first charge transport layer; an electrode layer, the electrode layer is arranged on the side of the second charge transport layer away from the perovskite absorption layer.

[0028] As mentioned above, the perovskite film of the present application has strong stability and photoelectric properties. Therefore, the perovskite solar cell of the present application has high photoelectric conversion efficiency. The stability of the perovskite film extends the service life of the solar cell and enables it to maintain long-term stability.

[0029] According to an embodiment of the present application, the first charge transport layer is a hole transport layer, and the second charge transport layer is an electron transport layer; or, the first charge transport layer is an electron transport layer, and the second charge transport layer is a hole transport layer.

[0030] In the fifth aspect of the present application, the present application proposes a perovskite tandem cell. According to an embodiment of the present application, the perovskite tandem cell comprises: a top cell and a bottom cell, the top cell is the perovskite solar cell described in the fourth aspect, and the top cell is arranged on the upper surface of the bottom cell.

[0031] In the sixth aspect of the present application, the present application proposes an electrical device. According to an embodiment of the present application, the electrical device includes the perovskite solar cell described in the fourth aspect or the perovskite tandem cell described in the fifth aspect.

[0032] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0034] Figure 1 is the specific structure of 2,2-bis(4-carboxyphenyl)hexafluoropropane according to the embodiments of the present application;

[0035] Figure 2 It is a schematic diagram of a perovskite film in which the upper and lower interfaces and surrounding interfaces are modified with a passivating agent according to an embodiment of the present application;

[0036] Figure 3 The method flow of interface modification of perovskite film according to the embodiment of the present application is Figure 1 ;

[0037] Figure 4 The method flow of interface modification of perovskite film according to the embodiment of the present application is Figure 2 ;

[0038] Figure 5 is a structural diagram of a perovskite solar cell according to an embodiment of the present application;

[0039] Figure 6 is a structural diagram of a perovskite solar cell containing a buffer layer according to an embodiment of the present application;

[0040] Description of the drawings: 001: substrate; 002: first charge transport layer; 003: perovskite absorption layer; 004: second charge transport layer; 005: electrode layer; 006: buffer layer. DETAILED DESCRIPTION

[0041] The following is a detailed description of the embodiments of the technical solution of the present application. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.

[0042] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0043] For simplicity, only some numerical ranges are specifically disclosed herein. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, and any upper limit can be combined with any other upper limit to form an unspecified range. In addition, each separately disclosed point or single value can itself be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an unspecified range.

[0044] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.

[0045] In this document, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present application.

[0046] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of this application, unless otherwise specified, the meaning of "plurality" is two or more.

[0047] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0048] Perovskite film and preparation method thereof

[0049] The present application proposes a perovskite film. According to an embodiment of the present application, the perovskite film is modified with a passivator, and the passivator includes a fluorine-containing symmetrical conjugated structure compound. Fluorine is an element with strong electronegativity, and the symmetrical conjugated structure generally has strong adsorption capacity and surface activity. Therefore, the use of a fluorine-containing symmetrical conjugated structure compound as a protective agent can ensure that it is effectively bonded and adsorbed on the surface of the perovskite film, thereby protecting the perovskite film.

[0050] According to an embodiment of the present application, the passivator is modified on the upper and lower interfaces and the surrounding interfaces of the perovskite film. By modifying the upper and lower interfaces and the surrounding interfaces of the perovskite film with a fluorine-containing symmetrical conjugated structure compound, multiple protection effects can be achieved, that is, these passivator modified layers can form a protective barrier to prevent external water and moisture from entering the interior of the perovskite film, effectively reduce the penetration of water, protect the perovskite film from water erosion, and achieve full enclosed protection of the perovskite film. In addition, these passivator modified layers can also improve the thermal stability and light stability of the perovskite film, which can not only reduce the pyrolysis temperature of the perovskite material and slow down the pyrolysis reaction, but also absorb and scatter part of the energy of the incident light, reduce the damage of the light energy to the perovskite film, and improve the long-term stability and performance of the perovskite solar cell.

[0051] In some embodiments of the present application, the fluorine-containing symmetrical conjugated structure compound includes at least one of 2,2-bis(4-aminophenyl)hexafluoropropane, 2,2-bis(4-carboxyphenyl)hexafluoropropane, 2,2-bis(3,4-xylyl)hexafluoropropane, 2,2-bis(3-nitrophenyl)hexafluoropropane, 2,2-bis(4-methylphenyl)hexafluoropropane, 2,2-bis(4-isocyanatophenyl)hexafluoropropane, 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane and 2,2-bis[4-(4-aminophenoxybenzene)]hexafluoropropane.

[0052] Among them, the structure of 2,2-bis(4-aminophenyl)hexafluoropropane is as follows:

[0053]

[0054] The structure of 2,2-bis(4-carboxyphenyl)hexafluoropropane is shown below:

[0055]

[0056] The structure of 2,2-bis(4-methylphenyl)hexafluoropropane is shown below:

[0057]

[0058] The structure of 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane is shown below:

[0059]

[0060] For example, when 2,2-bis(4-carboxyphenyl)hexafluoropropane is used for interface modification, Figure 1 As shown, the 3-F in the red box is strongly electronegative and has two strong electron-donating C=O atoms, which are respectively bonded to the FA in the perovskite layer. + and Pb 2+ The reaction adsorbs on the upper and lower surfaces and the surrounding areas. The benzene ring and the other three Fs can effectively reduce the erosion of external water due to their strong hydrophobicity. The schematic diagram of the perovskite film with the upper and lower interfaces and the surrounding interfaces modified with passivators is shown in the figure. Figure 2 As shown, the perovskite film is fully wrapped by the passivator to form a fully enclosed protection.

[0061] The present application proposes a method for interface modification of perovskite thin films. Figure 3 , the method comprising:

[0062] S100: Immersion treatment

[0063] In this step, the perovskite film to be modified is immersed in an organic solvent containing a passivating agent, so as to obtain a perovskite film with the upper interface and surrounding interfaces modified with the passivating agent.

[0064] Through this method, the upper interface and surrounding interfaces of the perovskite film can be effectively modified, and these modifications can achieve multiple protection effects, that is, these passivator modified layers can form a protective barrier to prevent external water and moisture from entering the interior of the perovskite film, effectively reduce the penetration of water, and protect the perovskite film from water erosion. In addition, these passivator modified layers can also improve the thermal stability and light stability of the perovskite film, not only can they reduce the pyrolysis temperature of the perovskite material and slow down the pyrolysis reaction, but they can also absorb and scatter part of the energy of the incident light, reduce the damage of the light energy to the perovskite film, and improve the long-term stability and performance of the perovskite solar cell.

[0065] In some embodiments of the present application, the soaking treatment time is 3s to 5s, for example, but not limited to, 3s, 4s, or 5s.

[0066] In some embodiments of the present application, the perovskite film to be modified is formed by performing a first coating treatment of a perovskite film material on a substrate. Wherein, the specific type of the above-mentioned substrate is not particularly limited, and a commonly used conductive glass substrate or a velvet substrate, or a hole transport layer can be used. Conductive glass, for example, can be ITO (indium tin oxide) transparent conductive glass, FTO (fluorine-doped tin oxide) transparent conductive glass, IWO (tungsten-doped indium oxide) transparent conductive glass and AZO (aluminum-doped zinc oxide) transparent conductive glass, etc., and the velvet substrate can be, for example, a crystalline silicon velvet substrate and other velvet substrates of a perovskite-silicon stacked solar cell. The hole transport layer can be formed on a conductive glass substrate or a velvet substrate by a precursor liquid spin coating method, a precursor liquid scraping method, a slit coating method, and the like.

[0067] In some embodiments of the present application, before the first coating treatment, a second coating treatment of an organic solvent containing a passivating agent is performed on the substrate; and the substrate coated with the organic solvent containing the passivating agent is subjected to a first annealing treatment. Therefore, a buried interface can be formed at the lower interface of the perovskite film, which can provide favorable conditions for the vertical growth of the perovskite layer. The formation of a buried interface can prevent the perovskite precursor in the solution from diffusing in the vertical direction, thereby prompting the perovskite layer to grow preferentially in the horizontal direction. This vertical growth mode helps to form a more uniform and continuous perovskite layer. In addition, the presence of a buried interface can also provide additional nucleus growth sites, which helps to increase the number and size of perovskite crystals. This helps to improve the overall crystallinity of the perovskite film, reduce the presence of grain boundaries and defects, and improve the film quality and photoelectric conversion performance.

[0068] In some embodiments of the present application, the first annealing treatment is performed at 100-110° C., for example but not limited to any one of 100° C., 101° C., 102° C., 103° C., 104° C., 105° C., 106° C., 107° C., 108° C., 109° C., 110° C., or any range between two thereof.

[0069] In some embodiments of the present application, the time of the first annealing treatment is 5 minutes to 7 minutes, for example but not limited to any one of 5 minutes, 6 minutes, 7 minutes, or a range between any two of them.

[0070] In some embodiments of the present application, the passivating agent includes a fluorine-containing symmetrical conjugated structure compound. Fluorine is an element with strong electronegativity, and the symmetrical conjugated structure generally has strong adsorption capacity and surface activity. Therefore, the use of a fluorine-containing symmetrical conjugated structure compound as a protective agent can ensure that it is effectively bonded to the upper and lower surfaces and surrounding surfaces of the perovskite film, thereby achieving full enclosed protection of the perovskite film.

[0071] In some embodiments of the present application, the symmetrical compound containing hexafluoropropane includes at least one of 2,2-bis(4-aminophenyl)hexafluoropropane, 2,2-bis(4-carboxyphenyl)hexafluoropropane, 2,2-bis(3,4-xylyl)hexafluoropropane, 2,2-bis(3-nitrophenyl)hexafluoropropane, 2,2-bis(4-methylphenyl)hexafluoropropane, 2,2-bis(4-isocyanatophenyl)hexafluoropropane, 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane and 2,2-bis[4-(4-aminophenoxybenzene)]hexafluoropropane.

[0072] Among them, the structure of 2,2-bis(4-aminophenyl)hexafluoropropane is as follows:

[0073]

[0074] The structure of 2,2-bis(4-carboxyphenyl)hexafluoropropane is shown below:

[0075]

[0076] The structure of 2,2-bis(4-methylphenyl)hexafluoropropane is shown below:

[0077]

[0078] The structure of 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane is shown below:

[0079]

[0080] For example, when 2,2-bis(4-carboxyphenyl)hexafluoropropane is used for interface modification, Figure 2 As shown, the 3-F in the red box is strongly electronegative and has two strong electron-donating C=O atoms, which are respectively bonded to the FA in the perovskite layer. + and Pb 2+ The reaction adsorbs on the upper and lower surfaces and the surrounding areas. The benzene ring and the other three Fs can effectively reduce the erosion of external water due to their strong hydrophobicity. The schematic diagram of the perovskite film with the upper and lower interfaces and the surrounding interfaces modified with passivators is shown in the figure. Figure 3 As shown, the perovskite film is fully wrapped by the passivator to form a fully enclosed protection.

[0081] In some embodiments of the present application, the organic solvent includes isopropanol, methanol or chlorobenzene. The organic solvent has good solubility and can effectively dissolve the passivating agent used for interface modification, so that the interface modifier can be evenly dispersed in the solution to achieve uniform modification of the perovskite film.

[0082] In some embodiments of the present application, the concentration of the passivator in the organic solvent is 0.5 mol / L to 1 mol / L. Therefore, the passivator can be evenly dispersed in the organic solvent, thereby achieving uniform modification of the perovskite film. For example, it can be but not limited to any one of 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L, 0.9 mol / L, 1.0 mol / L, or a range between any two of them.

[0083] In some embodiments of the present application, refer to the attached Figure 4 After the immersion treatment, the method further includes: performing a spin drying treatment on the perovskite film after the immersion treatment; and performing a second annealing treatment on the perovskite film after the spin drying treatment, so as to obtain a perovskite film with a passivator modified on the upper and lower interfaces and the surrounding interfaces.

[0084] In some embodiments of the present application, the spin drying process is performed at 4800 rpm to 5200 rpm, for example, but not limited to, any one of 4800 rpm, 4850 rpm, 4900 rpm, 4950 rpm, 5000 rpm, 5050 rpm, 5100 rpm, 5150 rpm, 5200 rpm, or any range therebetween.

[0085] In some embodiments of the present application, the spin drying time is 20s to 30s, for example, but not limited to, any one of 20s, 21s, 22s, 23s, 24s, 25s, 26s, 27s, 28s, 29s, and 30s, or a range between any two of them.

[0086] In some embodiments of the present application, the second annealing treatment is performed at 80° C. to 120° C. For example, it may be, but is not limited to, any one of 80° C., 85° C., 90° C., 95° C., 100° C., 105° C., 110° C., 115° C., 120° C., or any range between two thereof.

[0087] In some embodiments of the present application, the second annealing treatment time is 7 minutes to 10 minutes, for example, but not limited to, any one of 7 minutes, 8 minutes, 9 minutes, 10 minutes, or a range between any two of them.

[0088] The present application proposes a perovskite film. According to an embodiment of the present application, the perovskite film is prepared by the above-mentioned method. As mentioned above, the method of the present application can modify the upper and lower interfaces and the surrounding interfaces of the perovskite film to form a fully enclosed protective layer. Therefore, the perovskite film prepared by this method has strong stability, and the protective layer can prevent the perovskite film from contacting with adverse factors in the external environment (such as humidity, oxygen, light, etc.), reduce the damage and degradation to it, thereby extending the service life of the perovskite film; in addition, the perovskite film has good photoelectric properties and interface compatibility with other functional layers. The presence of the protective layer regulates the band structure, surface charge and interface electron transport characteristics of the perovskite film, thereby improving the photoelectric conversion efficiency, light absorption capacity and carrier transport efficiency.

[0089] Battery

[0090] The present application proposes a perovskite solar cell. According to an embodiment of the present application, referring to Figure 5 , the perovskite solar cell comprises:

[0091] Base 001;

[0092] A first charge transport layer 002, wherein the first charge transport layer 002 is disposed on one side of the substrate 001;

[0093] A perovskite absorption layer 003, wherein the perovskite absorption layer 003 comprises the aforementioned perovskite film, and the perovskite absorption layer 003 is arranged on a side of the first charge transport layer 002 away from the substrate 001;

[0094] A second charge transport layer 004, wherein the second charge transport layer 004 is disposed on a side of the perovskite absorption layer 003 away from the first charge transport layer 002;

[0095] The electrode layer 005 is arranged on a side of the second charge transport layer 004 away from the perovskite absorption layer 003 .

[0096] As mentioned above, the perovskite film of the present application has strong stability and photoelectric properties. Therefore, the perovskite solar cell of the present application has high photoelectric conversion efficiency. The stability of the perovskite film extends the service life of the solar cell and enables it to maintain long-term stability.

[0097] In some embodiments of the present application, the first charge transport layer 002 is a hole transport layer, and the second charge transport layer 004 is an electron transport layer.

[0098] In some embodiments of the present application, the first charge transport layer 002 is an electron transport layer, and the second charge transport layer 004 is a hole transport layer.

[0099] In some embodiments of the present application, reference Figure 6 The perovskite solar cell further includes: a buffer layer 006 , and the buffer layer 006 is arranged between the second charge transport layer 004 and the electrode layer 005 .

[0100] In some embodiments of the present application, the buffer layer 006 is disposed between the second charge transport layer 004 and the electrode layer 005. When the second charge transport layer 004 is a hole transport layer, the buffer layer can form an energy level gradient on the hole transport path to promote hole transport; the wide bandgap buffer layer material can also effectively inhibit the migration of electrons toward the anode, passivate the defect state of the interface, reduce carrier recombination, inhibit the migration of metal ions, and protect the perovskite absorption layer. When the second charge transport layer 004 is an electron transport layer, the main function of the buffer layer is to form an energy level gradient on the electron transport path to promote electron transport; inhibit the migration of metal ions and protect the perovskite absorption layer.

[0101] In some embodiments of the present application, the substrate may be a commonly used conductive glass substrate or a velvet substrate. The conductive glass may be, for example, ITO (indium tin oxide) transparent conductive glass, FTO (fluorine-doped tin oxide) transparent conductive glass, IWO (tungsten-doped indium oxide) transparent conductive glass, and AZO (aluminum-doped zinc oxide) transparent conductive glass, etc. The velvet substrate may be, for example, a crystalline silicon velvet substrate of a perovskite-silicon stacked solar cell and other velvet substrates.

[0102] In some embodiments of the present application, the perovskite material in the perovskite absorption layer is selected from the compounds represented by the following chemical formula: MA x FA 1-x PbI 3-a Br a 、MA x FA 1-x PbI 3-b Cl b 、MA x FA1-x PbB 3-c Cl c , FA 1-y Cs y PbI3、Cs x FA 1-x PbI 3-a Br a , where x and y are all between 0 and 1, and a, b, and c are all between 0 and 3; the chemical formula of MA is CH3NH 3+ , the chemical formula of FA is CH(NH2) 2+ Of course, it is understood that the perovskite material of the present invention is not limited to the above compounds, and can also be other perovskite materials that are deemed suitable by those skilled in the art. The perovskite absorption layer can be formed by evaporation, sputtering, chemical bath deposition, precursor liquid spin coating, precursor liquid scraping, slit coating, etc., and its thickness is 500nm to 700nm. This can further improve the performance of perovskite solar cells.

[0103] In some embodiments of the present application, the hole transport material in the hole transport layer may include but is not limited to one or more of the following materials and their derivatives: 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD), carbazoles, triphenylamines, polytriarylamine (PTAA), nickel oxide (NiOx), poly-3,4-ethylenedioxythiophene: polystyrene sulfonate (PEDOT:PSS), WO3 and other materials that can transport holes and block electrons. It can be formed by chemical bath deposition, precursor liquid spin coating, precursor liquid scraping, slit coating and other methods, and the preferred thickness of the hole transport layer is 15nm-30nm.

[0104] In some embodiments of the present application, the components of the electron transport layer may be electron transport materials commonly used in the art, including but not limited to [6,6]-phenyl-C 61 -Methyl butyrate (PC 61 BM), [6,6]-phenyl-C 71 -Methyl butyrate (PC 71 BM), fullerene C 60 , Fullerene C 70 , at least one of tin dioxide and zinc oxide, can be formed by evaporation, sputtering, chemical bath deposition, precursor liquid spin coating, precursor liquid scraping, slit coating and the like. The preferred thickness of the electron transport layer is 10 to 40 nm.

[0105] In some embodiments of the present application, the electrode layer is a metal electrode or a transparent electrode. The metal electrode may be, for example, a silver electrode (Ag), a copper electrode (Cu), a gold electrode (Au), an aluminum electrode (Al), a molybdenum electrode (Mo), or a chromium electrode (Cr); the transparent electrode may be, for example, tin-doped indium oxide (ITO), indium zinc oxide (IZO), tungsten-doped indium oxide (IWO), aluminum-doped zinc oxide (AZO), fluorine-doped tin oxide (FTO), zinc oxide, etc. The electrode layer may be formed by evaporation, sputtering, chemical bath deposition, precursor liquid spin coating, precursor liquid scraping, slit coating, etc., and the preferred thickness of the electrode layer is 60 to 100 nm.

[0106] In some embodiments of the present application, the material of the buffer layer includes one of bathocuproin (BCP) or tin dioxide (SnO2), and can be formed by evaporation, sputtering, chemical bath deposition, precursor liquid spin coating, precursor liquid scraping, slit coating, etc. The preferred thickness of the buffer layer is 1 to 10 nm.

[0107] The present application proposes a perovskite tandem cell. According to an embodiment of the present application, the perovskite tandem cell comprises: a top cell and a bottom cell, the top cell is the aforementioned perovskite solar cell, and the top cell is arranged on the upper surface of the bottom cell. Therefore, the perovskite tandem cell has all the advantages of a perovskite solar cell, which will not be described in detail here.

[0108] In some embodiments of the present application, the perovskite tandem cell can be selected from any one of a perovskite / crystalline silicon tandem cell, a full perovskite tandem cell, a perovskite / organic tandem cell, and a perovskite / CIGS tandem cell.

[0109] Electrical equipment

[0110] The present application proposes an electrical device. According to an embodiment of the present application, the electrical device has the aforementioned perovskite solar cell or the aforementioned perovskite stacked cell. Therefore, the electrical device has all the advantages of the perovskite solar cell, which will not be described in detail here.

[0111] Specifically, electrical equipment may include lighting elements, display elements, mobile devices, etc., and may specifically include street lights, signal indicators, insect killer lamps, electric fans, electric toys, electric tools, battery vehicles, electric vehicles, ships, spacecraft, etc., among which electric toys may include fixed or mobile electric toys, for example, game consoles, electric car toys, electric ship toys and electric airplane toys, etc., and spacecraft may include airplanes, rockets, space shuttles and spacecraft, etc.; photovoltaic power generation systems may include large-scale ground photovoltaic power generation systems, distributed photovoltaic power generation and building integrated photovoltaic power generation systems, etc.

[0112] The embodiments of the present application are described in detail below. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific technology or conditions are indicated in the embodiments, the technology or conditions described in the document in this area or the product specification are used. The reagents used or the instruments that do not indicate the manufacturer are all conventional products that can be obtained commercially.

[0113] Example 1

[0114] Step 1: Place the FTO substrate in an ultrasonic cleaning instrument and perform ultrasonic cleaning with deionized water and alcohol respectively (repeat the cleaning once), each step lasts for 15 minutes, and blow dry with a N2 gun for later use;

[0115] Step 2: NiOx powder is mixed in a ratio of (NiOx: deionized water) = (1:80), and the solution is repeatedly sonicated 3 times with an ultrasonic machine, each time for 5 minutes, to obtain a hole transport layer solution;

[0116] Step 3: The clean and spare FTO substrate in step 1 was subjected to UV-zone treatment for 20 minutes, and then the hole transport layer solution was spin-coated at a speed of 4000 rpm for 25 seconds and annealed at 150°C for 20 minutes to prepare a NiOx hole transport layer with a thickness of 25 nm;

[0117] Step 4: Dilute 2,2-bis(4-aminophenyl)hexafluoropropane powder in 1 ml of IPA (isopropyl alcohol) solution at a molar concentration of 0.75% to obtain a 2,2-bis(4-aminophenyl)hexafluoropropane interface modifier solution, referred to as NF-IPA, which is then spin-coated on the surface of the hole transport layer prepared in step 3 at a speed of 5000 rpm for 30 seconds, and annealed at 105° C. for 6 minutes, referred to as the NF layer, with a thickness of 6 nm;

[0118] Step 5: 1.5 mol FA 0.9 Cs 0.1 The drug powder of PbI3 was dissolved in 1 ml of an organic solvent with a volume ratio of DMF:DMSO = 4:1, and stirred for 2 h to obtain FA. 0.9 Cs 0.1 PbI3 precursor solution;

[0119] Step 6: Take 100 μL of the FA prepared in step 5 0.9 Cs 0.1 The PbI3 perovskite precursor solution was added dropwise to the NF layer prepared in step 4, extracted with an anti-solvent, and annealed at 150°C for 18 min to obtain FA. 0.9 Cs 0.1 PbI3 perovskite film, with a thickness of 600nm;

[0120] Step 7: Add the FA prepared in step 6 0.9 Cs 0.1 The PbI3 perovskite film was immersed in the NF-IPA solution prepared in step 4 for 4 seconds, and then the surface solvent was dried at a speed of 5000 rpm for 25 seconds, and then immediately annealed at 100°C for 8 minutes to obtain a fully covered NF layer;

[0121] Step 8: Substitute the FA obtained in step 7 0.9 Cs 0.1 30nm C was deposited on the surface of PbI3 perovskite film by thermal evaporation 60 As electron transport layer;

[0122] Step 9: BCP is thermally evaporated again on the electron transport layer in step 8. The main function of BCP is to act as a hole blocking layer to prevent electron-hole recombination. The thickness is 5 nm.

[0123] Step 10: The effective area of ​​evaporation on the BCP barrier layer prepared in step 9 is 0.071 cm 2 , with a thickness of 80nm, as the metal anode to prepare efficient FA 0.9 Cs 0.1 PbI3-NF perovskite solar cells.

[0124] Example 2

[0125] FA was prepared according to the method described in Example 1 0.9 Cs 0.1 The difference between PbI3-ACF perovskite solar cells lies in steps 4 and 7, as follows:

[0126] Step 4: Dilute 2,2-bis(4-carboxyphenyl)hexafluoropropane powder in 1 ml of IPA (isopropyl alcohol) solution at a molar concentration of 0.75% to obtain a 2,2-bis(4-carboxyphenyl)hexafluoropropane interface modifier solution, denoted as ACF-IPA, and then spin-coat it on the surface of the hole transport layer prepared in step 3 at a speed of 5000 rpm for 30 seconds, and anneal at 105° C. for 6 minutes, denoted as the ACF layer, with a thickness of 6 nm;

[0127] Step 7: Add the FA prepared in step 6 0.9 Cs 0.1 The PbI3 perovskite film was immersed in the ACF-IPA solution prepared in step 4 for 4 seconds, and then the surface solvent was dried at a rotation speed of 5000 rpm for 25 seconds, and immediately annealed at 100°C for 8 minutes to obtain a fully covered ACF layer.

[0128] Example 3

[0129] FA was prepared according to the method described in Example 1 0.9 Cs 0.1 The difference between PbI3-AF perovskite solar cells lies in steps 4 and 7, as follows:

[0130] Step 4: Dilute 2,2-bis(4-methylphenyl)hexafluoropropane powder in 1 ml of IPA (isopropyl alcohol) solution at a molar concentration of 0.75% to obtain a 2,2-bis(4-methylphenyl)hexafluoropropane interface modifier solution, denoted as AF-IPA, and then spin-coat it on the surface of the hole transport layer prepared in step 3 at a speed of 5000 rpm for 30 seconds, and anneal at 105° C. for 6 minutes, denoted as AF layer, with a thickness of 6 nm;

[0131] Step 7: Add the FA prepared in step 6 0.9 Cs 0.1 The PbI3 perovskite film was immersed in the AF-IPA solution prepared in step 4 for 4 seconds, and then the surface solvent was dried at a rotation speed of 5000 rpm for 25 seconds, and immediately annealed at 100°C for 8 minutes to obtain a full coverage AF layer.

[0132] Example 4

[0133] FA was prepared according to the method described in Example 1 0.9 Cs 0.1 The difference between PbI3-AA perovskite solar cells lies in steps 4 and 7, as follows:

[0134] Step 4: Dilute 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane powder in 1 ml of IPA (isopropyl alcohol) solution at a molar concentration of 0.75% to obtain 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane interface modifier solution, denoted as AA-IPA, and then spin-coat it on the surface of the hole transport layer prepared in step 3 at a speed of 5000 rpm for 30 seconds, and anneal at 105° C. for 6 minutes, denoted as AA layer, with a thickness of 6 nm;

[0135] Step 7: Add the FA prepared in step 6 0.9 Cs 0.1 The PbI3 perovskite film was immersed in the AA-IPA solution prepared in step 4 for 4 seconds, and then the surface solvent was dried at a rotation speed of 5000 rpm for 25 seconds, and immediately annealed at 100°C for 8 minutes to obtain a fully covered AA layer.

[0136] Example 5

[0137] FA was prepared according to the method described in Example 1 0.9 Cs 0.1 The difference between PbI3-DA perovskite solar cells lies in steps 4 and 7, as follows:

[0138] Step 4: Dilute 2,2-bis(3,4-xylyl)hexafluoropropane powder in 1 ml of IPA (isopropyl alcohol) solution at a molar concentration of 0.75% to obtain a 2,2-bis(3,4-xylyl)hexafluoropropane interface modifier solution, denoted as DA-IPA, and then spin-coat it on the surface of the hole transport layer prepared in step 3 at a speed of 5000 rpm for 30 seconds, and anneal at 105°C for 6 minutes, denoted as a DA layer, with a thickness of 6 nm;

[0139] Step 7: Add the FA prepared in step 6 0.9 Cs 0.1 The PbI3 perovskite film was immersed in the DA-IPA solution prepared in step 4 for 4 seconds, and then the surface solvent was dried at a rotation speed of 5000 rpm for 25 seconds, and immediately annealed at 100°C for 8 minutes to obtain a fully covered DA layer.

[0140] Example 6

[0141] FA was prepared according to the method described in Example 1 0.9 Cs 0.1 The difference between PbI3-TA perovskite solar cells lies in steps 4 and 7, as follows:

[0142] Step 4: Dilute 2,2-bis(3-nitrophenyl)hexafluoropropane powder in 1 ml of IPA (isopropyl alcohol) solution at a molar concentration of 0.75% to obtain a 2,2-bis(3-nitrophenyl)hexafluoropropane interface modifier solution, denoted as TA-IPA, and then spin-coat it on the surface of the hole transport layer prepared in step 3 at a speed of 5000 rpm for 30 seconds, and anneal at 105° C. for 6 minutes, denoted as a TA layer, with a thickness of 6 nm;

[0143] Step 7: Add the FA prepared in step 6 0.9 Cs 0.1 The PbI3 perovskite film was immersed in the TA-IPA solution prepared in step 4 for 4 seconds, and then the surface solvent was dried at a rotation speed of 5000 rpm for 25 seconds, and immediately annealed at 100°C for 8 minutes to obtain a fully covered TA layer.

[0144] Example 7

[0145] FA was prepared according to the method described in Example 10.9 Cs 0.1 PbI3-IA perovskite solar cell, the difference lies in step 4 and step 7, as follows:

[0146] Step 4: Dilute 2,2-bis(4-isocyanatophenyl)hexafluoropropane powder in 1 ml of IPA (isopropyl alcohol) solution at a molar concentration of 0.75% to obtain 2,2-bis(4-isocyanatophenyl)hexafluoropropane interface modifier solution, denoted as IA-IPA, and then spin-coat it on the surface of the hole transport layer prepared in step 3 at a speed of 5000 rpm for 30 seconds, and anneal at 105° C. for 6 minutes, denoted as IA layer, with a thickness of 6 nm;

[0147] Step 7: Add the FA prepared in step 6 0.9 Cs 0.1 The PbI3 perovskite film was immersed in the IA-IPA solution prepared in step 4 for 4 seconds, and then the surface solvent was dried at a rotation speed of 5000 rpm for 25 seconds, and immediately annealed at 100°C for 8 minutes to obtain a fully covered IA layer.

[0148] Example 8

[0149] FA was prepared according to the method described in Example 1 0.9 Cs 0.1 The difference between PbI3-TTA perovskite solar cells lies in steps 4 and 7, as follows:

[0150] Step 4: Dilute 2,2-bis[4-(4-aminophenoxybenzene)]hexafluoropropane powder in 1 ml of IPA (isopropyl alcohol) solution at a molar concentration of 0.75% to obtain a 2,2-bis[4-(4-aminophenoxybenzene)]hexafluoropropane interface modifier solution, denoted as: TTA-IPA, and then spin-coat it on the surface of the hole transport layer prepared in step 3 at a speed of 5000 rpm for 30 seconds, and anneal at 105°C for 6 minutes, denoted as the TTA layer, with a thickness of 6 nm;

[0151] Step 7: Add the FA prepared in step 6 0.9 Cs 0.1 The PbI3 perovskite film was immersed in the TTA-IPA solution prepared in step 4 for 4 seconds, and then the surface solvent was dried at a rotation speed of 5000 rpm for 25 seconds, and immediately annealed at 100°C for 8 minutes to obtain a fully covered TTA layer.

[0152] Example 9

[0153] FA was prepared according to the method described in Example 1 0.9 Cs0.1 The difference between PbI3-ACF-1 perovskite solar cell lies in step 4 and step 7, as follows:

[0154] Step 4: Dilute 2,2-bis(4-carboxyphenyl)hexafluoropropane powder in 1 ml of IPA (isopropyl alcohol) solution at a molar concentration of 0.5% to obtain 2,2-bis[4-(4-aminophenoxybenzene)]hexafluoropropane interface modifier solution, denoted as ACF-1-IPA, and then spin-coat it on the surface of the hole transport layer prepared in step 3 at a speed of 5000 rpm for 30 seconds, and anneal at 105°C for 6 minutes, denoted as ACF-1 layer, with a thickness of 6 nm;

[0155] Step 7: Add the FA prepared in step 6 0.9 Cs 0.1 The PbI3 perovskite film was immersed in the ACF-1-IPA solution prepared in step 4 for 4 seconds, and then the surface solvent was dried at a rotation speed of 5000 rpm for 25 seconds, and immediately annealed at 100°C for 8 minutes to obtain a fully covered ACF-1 layer.

[0156] Example 10

[0157] FA was prepared according to the method described in Example 1 0.9 Cs 0.1 The difference between PbI3-ACF-2 perovskite solar cell lies in step 4 and step 7, as follows:

[0158] Step 4: Dilute 2,2-bis(4-carboxyphenyl)hexafluoropropane powder in 1 ml of IPA (isopropanol) solution at a molar concentration of 1% to obtain 2,2-bis[4-(4-aminophenoxybenzene)]hexafluoropropane interface modifier solution, denoted as ACF-2-IPA, and then spin-coat it on the surface of the hole transport layer prepared in step 3 at a speed of 5000 rpm for 30 seconds, and anneal at 105°C for 6 minutes, denoted as ACF-2 layer, with a thickness of 6 nm;

[0159] Step 7: Add the FA prepared in step 6 0.9 Cs 0.1 The PbI3 perovskite film was immersed in the ACF-2-IPA solution prepared in step 4 for 4 seconds, and then the surface solvent was dried at a rotation speed of 5000 rpm for 25 seconds, and immediately annealed at 100°C for 8 minutes to obtain a fully covered ACF-2 layer.

[0160] Embodiment 11

[0161] FA was prepared according to the method described in Example 1 0.9 Cs0.1 The difference between PbI3-NF-1 perovskite solar cell lies in step 4 and step 7, as follows:

[0162] Step 4: Dilute 2,2-bis(4-aminophenyl)hexafluoropropane powder in 1 ml of MeOH (methanol) solution at a molar concentration of 0.75% to obtain a 2,2-bis(4-aminophenyl)hexafluoropropane interface modifier solution, denoted as NF-MeOH, and then spin-coat it on the surface of the hole transport layer prepared in step 3 at a speed of 5000 rpm for 30 seconds, and anneal at 105° C. for 6 minutes, denoted as NF-1 layer, with a thickness of 6 nm;

[0163] Step 7: Add the FA prepared in step 6 0.9 Cs 0.1 The PbI3 perovskite film was immersed in the NF-MeOH solution prepared in step 4 for 4 seconds, and then the surface solvent was dried at a rotation speed of 5000 rpm for 20 seconds to 30 seconds, and then immediately annealed at 100°C for 8 minutes to obtain a full coverage NF-1 layer.

[0164] Example 12

[0165] FA was prepared according to the method described in Example 1 0.9 Cs 0.1 The difference between PbI3-NF-2 perovskite solar cells lies in step 4 and step 7, as follows:

[0166] Step 4: Dilute 2,2-bis(4-aminophenyl)hexafluoropropane powder in 1 ml of CB (chlorobenzene) solution at a molar concentration of 0.75% to obtain a 2,2-bis(4-aminophenyl)hexafluoropropane interface modifier solution, referred to as NF-CB, which is then spin-coated on the surface of the hole transport layer prepared in step 3 at a speed of 5000 rpm for 30 seconds and annealed at 105°C for 6 minutes, referred to as NF-2 layer, with a thickness of 6 nm;

[0167] Step 7: Add the FA prepared in step 6 0.9 Cs 0.1 The PbI3 perovskite film was immersed in the NF-CB solution prepared in step 4 for 4 seconds, and then the surface solvent was dried at 5000 rpm for 25 seconds, and immediately annealed at 100°C for 8 minutes to obtain a fully covered NF-2 layer.

[0168] Comparative Example 1

[0169] FA was prepared according to the method described in Example 1 0.9 Cs 0.1The difference between the comparative example 1 and the embodiment 1 is that the comparative example 1 does not use the symmetrical conjugated structure compound to perform surrounding interface modification on the perovskite layer, and the specific steps are as follows:

[0170] Step 1: Place the FTO substrate in an ultrasonic cleaning instrument and perform ultrasonic cleaning with deionized water and alcohol respectively (repeat the cleaning once), each step lasts for 15 minutes, and blow dry with a N2 gun for later use;

[0171] Step 2: NiOx powder is mixed in a ratio of (NiOx: deionized water) = (1:80), and the solution is repeatedly sonicated 3 times with an ultrasonic machine, each time for 5 minutes, to obtain a hole transport layer solution;

[0172] Step 3: The clean and ready-to-use FTO conductive substrate in step 1 was subjected to UV-zone treatment for 20 minutes, and then the hole transport layer solution was spin-coated at a speed of 4000 rpm for 25 seconds and annealed at 150°C for 20 minutes to prepare a NiOx hole transport layer with a thickness of 25 nm;

[0173] Step 4: 1.5 mol FA 0.9 Cs 0.1 The drug powder of PbI3 was dissolved in 1 ml of an organic solvent with a volume ratio of DMF:DMSO = 4:1, and stirred for 2 h to obtain FA. 0.9 Cs 0.1 PbI3 precursor solution;

[0174] Step 5: Take 100 μL of the FA prepared in step 4 0.9 Cs 0.1 PbI3 perovskite precursor solution is added dropwise to the surface of the hole transport layer in step 3, extracted with an anti-solvent, and annealed at 150°C for 18 minutes to obtain FA 0.9 Cs 0.1 PbI3 perovskite film, with a thickness of 600nm;

[0175] Step 6: Substitute the FA obtained in step 5 0.9 Cs 0.1 30nm C was deposited on the surface of PbI3 perovskite film by thermal evaporation 60 As electron transport layer;

[0176] Step 7: BCP is thermally evaporated again on the electron transport layer in step 6. The main function of BCP is to act as a hole blocking layer to prevent electron-hole recombination. The thickness is 5 nm.

[0177] Step 8: The effective area of ​​evaporation on the BCP barrier layer prepared in step 7 is 0.071 cm 2, with a thickness of 80nm, as the metal anode to prepare efficient FA 0.9 Cs 0.1 PbI3 perovskite solar cells.

[0178] Comparative Example 2

[0179] FA was prepared according to the method described in Example 1 0.9 Cs 0.1 The difference between the comparative example 2 and the embodiment 1 is that the comparative example 2 uses other compounds to perform surrounding interface modification on the perovskite layer, and the difference is in step 4 and step 7, which are as follows:

[0180] Step 4: Dilute the methylamine lead bromide powder in 1 ml of CB (chlorobenzene) solution at a molar concentration of 0.75% to obtain a methylamine lead bromide interface modifier solution, denoted as MA-CB, and then spin-coat it on the surface of the hole transport layer prepared in step 3 at a speed of 5000 rpm for 30 seconds, and anneal at 105° C. for 6 minutes, denoted as MA layer, with a thickness of 6 nm;

[0181] Step 7: Add the FA prepared in step 6 0.9 Cs 0.1 The PbI3 perovskite film was immersed in the MA-CB solution prepared in step 4 for 4 seconds, and then the surface solvent was dried at a rotation speed of 5000 rpm for 25 seconds, and immediately annealed at 100°C for 8 minutes to obtain a fully covered MA layer.

[0182] Comparative Example 3

[0183] FA was prepared according to the method described in Example 1 0.9 Cs 0.1 The difference between the comparative example 3 and the embodiment 1 is that the comparative example 3 uses 2,2-bis(3,4-dimethylbenzene)hexafluoropropane as the interface modifier solution to modify only the upper and lower interfaces of the perovskite layer, and the specific process is as follows:

[0184] Step 1: Place the FTO substrate in an ultrasonic cleaning instrument and perform ultrasonic cleaning with deionized water and alcohol respectively (repeat the cleaning once), each step lasts for 15 minutes, and blow dry with a N2 gun for later use;

[0185] Step 2: NiOx powder is mixed in a ratio of (NiOx: deionized water) = (1:80), and the solution is repeatedly sonicated 3 times with an ultrasonic machine, each time for 5 minutes, to obtain a hole transport layer solution;

[0186] Step 3: The clean and spare FTO substrate in step 1 was subjected to UV-zone treatment for 20 minutes, and then the hole transport layer solution was spin-coated at a speed of 4000 rpm for 25 seconds and annealed at 150° C. for 20 minutes to prepare a NiOx hole transport layer;

[0187] Step 4: Dilute 2,2-bis(3,4-xylyl)hexafluoropropane powder in 1 ml of IPA (isopropyl alcohol) solution at a molar concentration of 0.75% to obtain 2,2-bis(4-aminophenyl)hexafluoropropane interface modifier solution, denoted as DA-IPA, and then spin-coat it on the surface of the hole transport layer prepared in step 3 at a speed of 5000 rpm for 30 seconds, and anneal at 105°C for 6 minutes, denoted as DA-1 layer, with a thickness of 6 nm;

[0188] Step 5: 1.5 mol FA 0.9 Cs 0.1 The drug powder of PbI3 was dissolved in 1 ml of an organic solvent with a volume ratio of DMF:DMSO = 4:1, and stirred for 2 h to obtain FA. 0.9 Cs 0.1 PbI3 precursor solution;

[0189] Step 6: Take 100 μL of the FA prepared in step 5 0.9 Cs 0.1 The PbI3 perovskite precursor solution was added dropwise to the DA-1 layer prepared in step 4, extracted with an anti-solvent, and annealed at 150°C for 18 min to obtain FA. 0.9 Cs 0.1 PbI3 perovskite film, with a thickness of 600nm;

[0190] Step 7: FA prepared in step 6 0.9 Cs 0.1 The DA-IPA solution prepared in step 4 was spin-coated on the surface of the PbI3 perovskite film for 30 seconds and annealed at 105°C for 6 minutes, which was recorded as the DA-2 layer with a thickness of 6 nm.

[0191] Step 8: Substitute the FA obtained in step 6 0.9 Cs 0.1 30nm C was deposited on the surface of PbI3 perovskite film by thermal evaporation 60 As electron transport layer;

[0192] Step 9: BCP is thermally evaporated again on the electron transport layer in step 8. The main function of BCP is to act as a hole blocking layer to prevent electron-hole recombination. The thickness is 5 nm.

[0193] Step 10: The effective area of ​​evaporation on the BCP barrier layer prepared in step 9 is 0.071 cm 2 , with a thickness of 80nm, as the metal anode to prepare efficient FA 0.9 Cs 0.1 PbI3-3 perovskite solar cells.

[0194] Comparative Example 4

[0195] FA was prepared according to the method described in Example 1 0.9 Cs 0.1 PbI3-3 perovskite solar cell, the difference between comparative example 3 and embodiment 1 is that comparative example 3 uses methylamine lead bromide as an interface modifier to only modify the upper and lower interfaces of the perovskite layer, and the specific process is as follows:

[0196] Step 1: Place the FTO substrate in an ultrasonic cleaning instrument and perform ultrasonic cleaning with deionized water and alcohol respectively (repeat the cleaning once), each step lasts for 15 minutes, and blow dry with a N2 gun for later use;

[0197] Step 2: NiOx powder is mixed in a ratio of (NiOx: deionized water) = (1:80), and the solution is repeatedly sonicated 3 times with an ultrasonic machine, each time for 5 minutes, to obtain a hole transport layer solution;

[0198] Step 3: The clean and spare FTO substrate in step 1 was subjected to UV-zone treatment for 20 minutes, and then the hole transport layer solution was spin-coated at a speed of 4000 rpm for 25 seconds and annealed at 150° C. for 20 minutes to prepare a NiOx hole transport layer;

[0199] Step 4: Dilute the methylamine lead bromide powder in 1 ml of CB (chlorobenzene) solution at a molar concentration of 0.75% to obtain a methylamine lead bromide interface modifier solution, denoted as MA-CB, and then spin-coat it on the surface of the hole transport layer prepared in step 3 at a speed of 5000 rpm for 30 seconds, and anneal at 105° C. for 6 minutes, denoted as MA-1 layer;

[0200] Step 5: 1.5 mol FA 0.9 Cs 0.1 The drug powder of PbI3 was dissolved in 1 ml of an organic solvent with a volume ratio of DMF:DMSO = 4:1, and stirred for 2 h to obtain FA. 0.9 Cs 0.1 PbI3 precursor solution;

[0201] Step 6: Take 100 μL of the FA prepared in step 5 0.9 Cs 0.1The PbI3 perovskite precursor solution was added dropwise to the MA-1 layer prepared in step 4, extracted with an anti-solvent, and annealed at 150°C for 18 min to obtain FA. 0.9 Cs 0.1 PbI3 perovskite film, with a thickness of 600nm;

[0202] Step 7: FA prepared in step 6 0.9 Cs 0.1 The MA-CB solution prepared in step 4 was spin-coated on the surface of the PbI3 perovskite film for 30 seconds and annealed at 105°C for 6 minutes, which was recorded as the MA-2 layer with a thickness of 6 nm.

[0203] Step 8: Substitute the FA obtained in step 6 0.9 Cs 0.1 30nm C was deposited on the surface of PbI3 perovskite film by thermal evaporation 60 As electron transport layer;

[0204] Step 9: BCP is thermally evaporated again on the electron transport layer in step 8. The main function of BCP is to act as a hole blocking layer to prevent electron-hole recombination. The thickness is 5 nm.

[0205] Step 10: The effective area of ​​evaporation on the BCP barrier layer prepared in step 9 is 0.071 cm 2 , with a thickness of 80nm, as the metal anode to prepare efficient FA 0.9 Cs 0.1 PbI3-4 perovskite solar cells.

[0206] The modified compounds and organic solvents used in Examples 1 to 13 and Comparative Examples 1 to 3 are shown in Table 1.

[0207] Table 1

[0208]

[0209]

[0210] Test experiment

[0211] The humidity stability, thermal stability and ultraviolet stability of the perovskite solar cells prepared in Examples 1 to 12 and Comparative Examples 1 to 4 were investigated.

[0212] The humidity stability results are shown in Table 2. Different perovskite solar cells were placed under unpackaged conditions at 23°C and 45% RH for 600 hours. Compared with the use of other compounds to modify the upper and lower interfaces and the surrounding interfaces of the perovskite film in Comparative Example 1, the method of the present application, that is, the use of fluorine-containing symmetrical conjugated structure compounds to modify the upper and lower interfaces and the surrounding interfaces of the perovskite film, the humidity stability of the perovskite solar cell prepared by the fully enclosed and protected perovskite film is significantly increased. In addition, compared with Comparative Examples 2 to 4, the perovskite film is not interface modified or only the upper and lower interfaces of the perovskite film are modified. After the perovskite film is fully enclosed and protected, the humidity stability of the perovskite solar cell prepared is better.

[0213] The thermal stability results are shown in Table 3. Different perovskite solar cells were placed at 85°C and heated continuously for 1000 hours. Compared with the use of other compounds to modify the upper and lower interfaces and the surrounding interfaces of the perovskite film in Comparative Example 1, the method of the present application, that is, the use of fluorine-containing symmetrical conjugated structure compounds to modify the upper and lower interfaces and the surrounding interfaces of the perovskite film, the thermal stability of the perovskite solar cell prepared by the fully enclosed protected perovskite film is significantly increased. In addition, compared with Comparative Examples 2 to 4, no interface modification is performed or only the upper and lower interfaces of the perovskite film are modified. After the perovskite film is fully enclosed and protected, the thermal stability of the perovskite solar cell prepared is better.

[0214] The UV stability results are shown in Table 4. 2 UV irradiation for 32 hours. Compared with the use of other compounds to modify the upper and lower interfaces and the surrounding interfaces of the perovskite film in Comparative Example 1, the method of the present application, that is, the use of fluorine-containing symmetrical conjugated structure compounds to modify the upper and lower interfaces and the surrounding interfaces of the perovskite film, the ultraviolet stability of the perovskite solar cell prepared by the fully enclosed and protected perovskite film is significantly increased. In addition, compared with Comparative Examples 2 to 4, no interface modification is performed or only the upper and lower interfaces of the perovskite film are modified, and the perovskite film is fully enclosed and protected, and the ultraviolet stability of the prepared perovskite solar cell is better.

[0215] Table 2 Humidity stability data of different perovskite solar cells

[0216]

[0217]

[0218] Table 3 Thermal stability data of different perovskite solar cells

[0219] Battery efficiency after 1000h Example 1 81.2% Example 2 83.4% Example 3 72.6% Example 4 81% Example 5 71.9% Example 6 73.7% Example 7 74.9% Example 8 68.2% Example 9 70.3% Example 10 72.7% Embodiment 11 80.8% Example 12 83.2% Comparative Example 1 59.4% Comparative Example 2 65.8% Comparative Example 3 66.4% Comparative Example 4 54.9%

[0220] Table 4 UV thermal stability data of different perovskite solar cells

[0221]

[0222]

[0223] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0224] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A perovskite film, characterized in that: The perovskite film is modified with a passivator, and the passivator includes a fluorine-containing symmetrical conjugated structure compound.

2. The perovskite film according to claim 1, characterized in that The passivating agent modifies the upper and lower interfaces and the surrounding interfaces of the perovskite film.

3. A method for interface modification of perovskite film, characterized in that: include: The perovskite film to be modified is immersed in an organic solvent containing a passivating agent to obtain a perovskite film with the passivating agent modified on all sides of the interface.

4. The method according to claim 3, characterized in that The perovskite film to be modified is formed by performing a first coating process of a perovskite film material on a substrate.

5. The method according to claim 4, characterized in that Before performing the first coating treatment, performing a second coating treatment of an organic solvent containing a passivating agent on the substrate; and The substrate coated with the organic solvent containing the passivating agent is subjected to a first annealing process.

6. The method according to any one of claims 3 to 5, characterized in that: The passivating agent comprises a fluorine-containing symmetrical conjugated structure compound.

7. The method according to claim 6, characterized in that The fluorine-containing symmetrical conjugated structure compound includes at least one of 2,2-bis(4-aminophenyl)hexafluoropropane, 2,2-bis(4-carboxyphenyl)hexafluoropropane, 2,2-bis(3,4-xylyl)hexafluoropropane, 2,2-bis(3-nitrophenyl)hexafluoropropane, 2,2-bis(4-methylphenyl)hexafluoropropane, 2,2-bis(4-isocyanatophenyl)hexafluoropropane, 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane and 2,2-bis[4-(4-aminophenoxybenzene)]hexafluoropropane.

8. The method according to any one of claims 3 to 5, characterized in that: The organic solvent includes isopropanol, methanol or chlorobenzene; and / or, the concentration of the passivating agent in the organic solvent is 0.5 mol / L to 1 mol / L; And / or, the immersion treatment time is 3s to 5s.

9. The method according to claim 3, characterized in that: Further including: The perovskite film after the immersion treatment is subjected to spin drying; as well as The spin-dried perovskite film is subjected to a second annealing treatment.

10. The method according to claim 9, characterized in that The spin drying process is carried out at 4800 rpm to 5200 rpm; And / or, the spin drying time is 20s to 30s; And / or, the second annealing treatment is performed at 80° C. to 120° C.; And / or, the second annealing treatment time is 7 minutes to 10 minutes.

11. The method according to claim 5, characterized in that The first annealing treatment is performed at 100-110°C; And / or, the first annealing treatment time is 5 minutes to 7 minutes.

12. A perovskite film, characterized in that: The method is prepared by any one of claims 3 to 11.

13. A perovskite solar cell, characterized in that: include: substrate; a first charge transport layer, wherein the first charge transport layer is disposed on one side of the substrate; A perovskite absorption layer, wherein the perovskite absorption layer comprises the perovskite thin film according to claim 12, and the perovskite absorption layer is arranged on a side of the first charge transport layer away from the substrate; a second charge transport layer, wherein the second charge transport layer is arranged on a side of the perovskite absorption layer away from the first charge transport layer; An electrode layer is disposed on a side of the second charge transport layer away from the perovskite absorption layer.

14. The perovskite solar cell according to claim 13, characterized in that: The first charge transport layer is a hole transport layer, and the second charge transport layer is an electron transport layer; Alternatively, the first charge transport layer is an electron transport layer, and the second charge transport layer is a hole transport layer.

15. An electrical equipment, characterized in that: Includes the perovskite solar cell according to claim 13 or 14.